Experimental investigation and identification of the transition boundary of churn and annular flows using multi-range differential pressure and conductivity signals. (5th March 2017) - Chen, Shao-Wen; Lin, Min-Song; Kuo, Feng-Jiun; Chai, Min-Lun; Liu, Shih-Yung; Lee, Jin-Der; Pei, Bau-Shei
Highlights: An air-water two-phase flow experiment was carried out for churn and annular flows. Transient pressure and void signals were analyzed with PDF, FFT and STD techniques. Pressure and void STD meshes can show different trends in churn and annular flows. A simple and efficient way for flow regime identification was proposed and compared. Abstract: In this study, an upward air-water two-phase flow experiment was carried out with a transparent circular tube to investigate the flow characteristics of churn and annular flows. A simple and novel method utilizing the transient differential pressure and conductivity signals were proposed to identify the transition boundary of churn and annular flows. The test range covers the flow conditions of superficial gas and liquid velocities of J g ≈ 5.1–30 m/s and J f ≈ 0.04–0.4 m/s under the atmospheric pressure, and the statistical techniques including PDF, FFT and STD mesh plots were used to present the flow characteristics. According to the present experimental results, the churn flow may transform to annular flow at the transition boundary of J g ≈ 12.6–15.7 m/s under the low liquid flow condition of J f ⩽ 0.4 m/s. The present results were benchmarked with the existing flow regime maps including Mishima-Ishii and Taitel-Dukler maps, and the identified transition boundary of churn to annular flows shows a good agreement with the existing maps. The present method can provide a simple and efficient way to identify the flow regimes.